Impact of Electron Beam Irradiation on Thermoplastic Polyurethanes Unraveled by Thermal Field-Flow Fractionation. (January 2021) - Geisler, Martin; Pal, Tuhin Subhra; Arnhold, Kerstin; Malanin, Mikhail; Müller, Michael Thomas; Voit, Brigitte; Pionteck, Jürgen; Lederer, Albena
Highlights: Different impact of electron beam irradiation on aliphatic and aromatic thermoplastic polyurethanes. Degradation, chain scission snd crosslinking depends on irradiation dose and temperature. ThFFF as an alternative approach for advanced analysis of crosslinked polymer structures. Abstract: The impact of electron beam irradiation on thermoplastic polyurethane material was studied for both an aliphatic and an aromatic polyurethane with approximately equal molar amount of hard and soft segments. Irradiation doses up to 300 kGy (kilogray) at room temperature and at 100 °C were applied. Changes in chemical structure, molar mass and size were assessed using infrared spectroscopy, differential scanning calorimetry, size-exclusion chromatography and thermal field-flow fractionation. Material alterations were correlated with trends regarding to degradation, crosslinking or branching changes. Thereby, limits of characterization by size exclusion chromatography are addressed and amended by thermal field-flow fractionation studies. In addition, a thermophoretic analysis has been carried out complementary to the portfolio of analytical methods applied in this work.